Impacto da utilização de um software educativo para conhecimento e redução de complicações secundárias à lesão por pressão: estudo multimétodos - Santos, Ana Paula Aragão (2022)
Introduction: patients with pre-existing pressure injuries or those acquired in the hospital environment need continuity of care at home, in order to promote healing and avoid complications such as infection and chronification of the lesion. The use of resources, such as educational software that assist in health education can strengthen self-care actions and are known to be efficient in preventing complications. Objective: to analyze the impact of the use of an educational software in the reduction of complications that compromise the healing of pressure injuries at home and in the reduction of readmissions. Method: study mix method with 4 sequential and interdependent phases. In phase 1, an integrative review was built as a basis for educational information made available in the software built in the subsequent phase. Phase 2 consisted of the construction of an educational application that was titled "Minha Pele" and after the completion of the prototype, phase 3 was carried out, the usability validation with experts in the area, through System Usability Scale, obtaining a final validation average of 83,25, rating it as excellent. In phase 4, a quasi-experiment was carried out with pre- and posttest in a single group, conducted with patients from the clinical inpatient units of two hospitals in the State of Sergipe. Data collection took place between the months of June 2021 and March 2022, at which time of discharge, the educational application was made available to patients and/or caregivers, and guidance on its use was provided. They were also evaluated for the risk of dermatitis, knowledge about pressure injury prevention, the injury was assessed using the Pressure Ulcer Scale for Healing and risk stratification was performed using Braden. The knowledge assessment and scar evolution instruments were reapplied after 30 days of application use. Results: 78 patients participated in the study, the average percentage of correct answers in the pre-test of knowledge about pressure injury prevention in the pre-test was 79.2% (SD ± 8.7) and in the post-test 80.5% ( SD ± 10.8). The healing evolution according to the PUSH (p-0.0000²) pre and post test showed significance. When the death outcome was evaluated, risk stratification according to Braden showed a statistically significant association (p-0.022). Conclusion: The use of the educational application improves the evolution of healing, increases caregivers' knowledge about prevention and overcomes accessibility and monitoring barriers, which reduces the risk of complications and consequently the risk of readmissions.